Maternal and perinatal mortality in the district of Yauli, Huancavelica. 1997. - Tejada, Roxana (2015)
To determine the main factors associated with high maternal and perinatal mortality Yauli District. MATERIALS AND METHODS: Between January and December 1997, an active search of death recording level not only of health but also from the records of the 32 communities in the District of Yauli was performed. Surveys to 100% of mothers and / or parents, home of the mother and / or father was made. RESULTS: underreporting of 285% was found. The maternal mortality rate was 1008 per hundred thousand live births and perinatal 75 per thousand live births. All maternal deaths were from direct obstetric causes, of which 71% was from hemorrhage due to retained placenta. 100% of maternal deaths were attributed magical cause, 42% were from the age group of 25-29 years, 71% and 100% illiterate Quechua speakers, 57% had a intergenesic period of two years, all they were attended by her husband and only advised the health personnel it finds to death. As perinatal deaths, stillbirths were 30.7%, 28.8% preterm. Of stillbirths, 43.7% was breech. All were treated in their homes and 96% by a family member. Husbands do not let any man see or touch his wife; moreover, it is customary for women home birth and see no need of prenatal care. CONCLUSIONS: The rates of maternal mortality and perinatal Yauli district is 3 to 4 times higher than national attention for health personnel to the mother and the newborn is low and the search for them is minimal. The husband is preferably decides, serving women, which should lead to propose new strategies to reduce the high mortality present in the district.